Caracterização dos aspectos clínicos,epidemiológicos e lesões associadas à luxação de patela em cães atendidos no Hospital Veterinário no período de 2000 a 2010: estudo retrospectivo - Juliana Soares Lara (2011)
The objective of this study was report, through a retrospective study, the patellar and articular lesions associated with patellar luxation in dogs and to correlate them with body mass, the animals age and the degree of luxation. Its also to report the most affected breeds, the clinical history, the frequency in relation to sex, age, body mass and degree of luxation, the surgical techniques used and the occurrence of postoperative luxation associated with patellar luxation in dogs presented for treatment in Veterinary Hospital of UFMG in the period from 2000 to 2010. After a survey of clinical and surgical records of dogs with patellar dislocation, 210 animals and 342 joints were student. Among them, 88.3% (n = 302) showed medial luxation and 11,7% (n = 40) presented lateral luxation. The most affected breeds were Poodle, Yorkshire, Pinscher and mongrel dogs. All luxation were called congenital. The bilateral luxation was significantly more frequent in relation to the unilateral one, with 76% of the cases. Females were more affected than males at a ratio of 1.5:1. The age of the animals ranged from 32 days to 16 years, with significant increase in patellar luxation in animals under one year old and less than 9.1 kg. In 40 members (11.7%) there was a grade I dislocation, in 136 (39.8%) there was a grade II dislocation, in 70 (20.5%) there was a grade III dislocation and in 96 (28%) there was a grade IV dislocation. The frequency of preoperative lameness was hight in luxation degrees III and IV, and from the beginning of the lameness until the clinical evaluation varied from 2 to 288 weeks. Among 342 joints, 218 were treated surgically. Lesions such as the erosion of the joint cartilage were observed as in one quarter (16.8%), half (14%) or the entire length of the patella (2.3%), exposure of subchondral bone (3.8%), flat surface patellar (11.7%) or concave (7.3%) and presence of entesófitos (11.7%). The joint changes were synovitis (37.9%), osteophytes (39.6%), rasamento trochlear groove (86%), absence of trochlea (16.8%), erosion of condylar edge (62.4%), exposure of subchondral bone (9.04%), thickening of the joint capsule (27.2%), injury of the long digital extensor tendon (2.7%), cranial crossed ligament rupture (9,3%) and meniscus prolapse (3.1%). Patellar and joint lesions were most commonly observed in luxation grades II and III. Animals with body mass index over 20Kg were most affected by patellar and joint injuries, and patellar lesions were more frequent in animals older than 24 months. In the first 60 postoperative days, animals with grade IV luxation showed higher frequency of severe claudication. After this period, most animals showed normal ambulation in all grades. Recurrence of luxation after surgery had no effect on the degree of dislocation, body weight and the type of luxation (medial or lateral). The cranial cruciate ligament rupture associated with luxation of the patella was not influenced by the degree of luxation. It is concluded that all degrees og luxation should be treated because they often trigger patellar and joint changes. Animals with body mass over 20kg and/or luxation with degree IV have a reserved prognosis regarding the recovery of limb function an need physical therapy rehabilitation and frequent monitoring. Dogs with patellar luxation and older than seven years old are more predisposition cruciate ligament rupture.